Multiple species comparison of cardiac troponin T and dystrophin: unravelling the DNA behind dilated cardiomyopathy - England, Jennifer; Loughna, Siobhan; Rutland, Catrin S. (MDPI, 2017)
Animals have frequently been used as models for human disorders and mutations. Following advances in genetic testing and treatment options, and the decreasing cost of these technologies in the clinic, mutations in both companion and commercial animals are now being investigated. A recent review highlighted the genes associated with both human and non-human dilated cardiomyopathy. Cardiac troponin T and dystrophin were observed to be associated with both human and turkey (troponin T) and canine (dystrophin) dilated cardiomyopathies. This review gives an overview of the work carried out in cardiac troponin T and dystrophin to date in both human and animal dilated cardiomyopathy.